Conflict and Media Framing: The Case of Detik.com News towards Rohingya Conflict - Ahmad Ali Afandi; Hammad Isyroqun; Badrus Sholeh (Jurnal Transformasi Global, 2024)
This study analyzes the framing strategies used by Detik.com in covering the Rohingya conflict using the Robert N. Entman approach. Through an analysis of a number of published news, it was found that Detik.com tend to portray the crackdown by the Myanmar government as a violation of human rights and international law. The reports highlighted the systematic violence and persecution experienced by the Rohingya community, describing it as a form of oppression perpetrated by the Myanmar regime against the Muslim minority. This framing positions the Rohingya community as victims and exposes Myanmar as the main perpetrator of international human rights violations. Detik.com framing strategy not only focuses on describing events, but also emphasizes the violent relationship between the Myanmar government and the Rohingya community as an issue that requires international attention. Through reports that emphasize the need for international intervention and protection for the Rohingya community, Detik.com directed its audience to condemn the actions of the Myanmar regime and support solutions oriented towards the protection of the rights of the Rohingya community. In addition, Detik.com also showed the solutions offered, which are more likely to favor independence and the return of Rohingya refugees to Myanmar in safe conditions. Using Robert N. Entman's framing theory, the study reveals how Detik.com frame the Rohingya conflict as an issue related to human rights, international law, and the need for international intervention to protect victims. This framing not only exposes the reality of the violence experienced by the Rohingya, but also illustrates the need for global action to ensure long-term protection for the Rohingya community who continue to live in insecurity.